Failure analysis of Co–Cr hip resurfacing prosthesis during solidification - Alvarez Vera, Melvyn; García Duarte, José Hilario; Juárez Hernández, Arturo; Mercado Solis, Rafael David; Castillo, A. G.; Hernández Rodríguez, Marco Antonio Loudovic (2013)
In this study a failure originated during solidification process into the femoral stem component of Hip Resurfacing prosthesis was investigated. Visual inspection, optical microscopy, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and a commercial software simulation ProCAST were carried out in order to determine the cause and solution of this failure. The results exhibited hot tearing, shrinkage porosity and metal oxide films due to inadequate heat dissipation during solidification process, as a consequence of poor investment casting ceramic mold configuration. Also in this paper was improved the casting design solving this kind of defects.